2004
DOI: 10.1080/00365590310006237
|View full text |Cite
|
Sign up to set email alerts
|

Can prostate biopsies predict suitability for nerve‐sparing radical prostatectomy?

Abstract: Biopsy-suggested "unilateral" carcinoma was associated with both a high incidence of "bilateral" disease on final histology following radical prostatectomy and an alarming incidence (24%) of positive surgical margins on the "benign" side where NSRP might be advocated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Sanwick et al [4] expanded the preoperative biopsy criteria by including moderategrade unilateral tumours of patients having at least three biopsy cores on the noncancerous side. The same authors however reported that no safe parameters for considering nerve-sparing surgery were observed in patients with high-grade tumours, in any specimen with cancer present on biopsy, a finding which is in accordance with later observations [5] . Therefore, we feel that the patient selection based on histological differentiation criteria in order to perform NSRP is probably not safe because of the multifocality and heterogeneity of prostate cancer [6] .…”
supporting
confidence: 78%
“…Sanwick et al [4] expanded the preoperative biopsy criteria by including moderategrade unilateral tumours of patients having at least three biopsy cores on the noncancerous side. The same authors however reported that no safe parameters for considering nerve-sparing surgery were observed in patients with high-grade tumours, in any specimen with cancer present on biopsy, a finding which is in accordance with later observations [5] . Therefore, we feel that the patient selection based on histological differentiation criteria in order to perform NSRP is probably not safe because of the multifocality and heterogeneity of prostate cancer [6] .…”
supporting
confidence: 78%
“…Connolly et al. [6] attempted to use prostate biopsy data to predict the suitability for nerve‐sparing RP. In their series, 85% of men with unilateral disease on biopsy had pathological bilateral cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that up to 74% of prostatectomy specimens with unilaterally positive biopsies have tumor in the contralateral side, with PSMs rates on the biopsy-shown ‘benign’ side from 24–31%. 13,14 Despite these concerns, single-institution studies have not shown NS RP to be an independent risk factor for PSMs or biochemical recurrence. 1518 …”
Section: Discussionmentioning
confidence: 99%